Passions and the Struggle Against Them According to Mark the Hermit - Nieścior, Leon (Collectanea Theologica, 2021)
Mark the Hermit, a monk from the 4th century, active probably in Asia Minor, indicates in an original way that the cause of passion in man is forgetting about good thoughts (lēthē), carelessness (rhathymia) and ignorance (agnoia). This threefold evil is opposed by the following means: forgetfulness – by memory of good works, carelessness – by most sincere readiness, ignorance – by enlightened cognition. Nobody before him had ever dealt with the causes of passion in such a way and indicated such an antidote to them. In order to understand Mark the Hermit’s theory, it is necessary to look in detail at this writer’s teaching about passion and the ascetic fight against it. This article is devoted to this spiritually important issue.